(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Quality of patient care must not be overlooked even though the domain of patient care at present is fast growing. Ward supervisors are the front line leaders of nursing staff in care of patients in the hospital and they are at the middle level of management. They create an environment that ensures the delivery of safe and high-quality patient care, high patient satisfactory rates, and positive patient outcomes. This study was made to evaluate the quality of nursing care in hospitals by measuring patient care satisfaction with the managerial roles of the ward supervisors taken into consideration; no studies have yet been formally conducted among hospitals in Zamboanga City. The study conducted was a descriptive correlational design that focused on the management practices of ward supervisors and its relationship on patient care satisfaction at Hospital X in Zamboanga City. The respondents will composed of 100 staff nurses who will evaluate the management practices of ward supervisors and 100 adult patients who will evaluate the nursing care provided by the staff nurses. The study will utilize the non-probability, purposive sampling method. The researcher utilized the Pearson product moment to identify the relationship of the two identified variables. In the conclusion, the nursing staffs were satisfied of the ward supervisors’ management practices as well as the patients were also satisfied with the nursing care received from the staff nurses. Although the results were remarkable, the study reveals that the there was no relationship between the ward supervisors management practices and the level of patient care satisfaction at Hospital X. The recommendation is to develop training design for leadership and management for ward supervisors to much more improve the skills in management of their respective areas to help motivate the staff nurses in their nursing care provided to patients.